MASA DEPAN TOLERANSI: “A Common Word” Di Kalangan Pelajar Sekolah Menengah Di Kota Pekalongan - Akhwanudin, Afith (Wahana Islamika: Jurnal Studi Keislaman, 2024)
The tolerant character of future generations is important in an increasingly heterogeneous society. They must have a vision that is able to work together beyond ethnic and religious differences. This research discusses the understanding and commitment of senior high school students in the city of Pekalongan regarding the universal human values ​​taught in each religion which are the basis for tolerance between humans as creatures. This research tried to find senior high school students’ understanding of the values ​​of "A Common Word" (kalimatussawa) which includes love of God and love of neighbours so the implementation of those understandings with a tolerant attitude and the desire to advance the nation together with believers of other religions. This research also tried to discover how the social structure of the high school community was built through externalization, objectification and internalization. The data was obtained through questionnaires to high school students at MAN Insan Cendekia Pekalongan and SMA N 4 Pekalongan as the main data which was then analysed through data reduction, data presentation and conclusion.  The research concluded that high school students in the city of Pekalongan have a very good understanding of “a common word” so implement the values in their daily lives with a strong commitment to advancing the country together with others by prioritizing social welfare. The social structure of senior high school students is greatly influenced by schools from the stages of externalization, objectification to internalization, where schools deliberately create external realities to get the feel of student identities that are humanist, tolerant, progressive.